Factors associated with the sensitivity of fine‐needle aspiration cytology for the diagnosis of follicular variant papillary thyroid carcinoma. (18th November 2015) - Chai, Young Jun; Suh, Hyunsuk; Yi, Jin Wook; Yu, Hyeong Won; Lee, Joon‐Hyop; Kim, Su‐jin; Won, Jae‐Kyung; Lee, Kyu Eun
Abstract : Background: The purpose of this study was to evaluate the factors associated with diagnostic accuracy of preoperative fine‐needle aspiration (FNA) for follicular variant papillary thyroid carcinoma (FVPTC). Methods: The patients with FVPTC who underwent thyroidectomy were divided into 2 groups: "group A" (Bethesda category II, III, or IV) versus "group B" (category V or VI). Results: A total of 225 patients (117 in group A and 108 in group B) were included. Group B was associated with older age, malignant ultrasonographic features, smaller tumor size, extrathyroidal extension, higher stage, and B‐type Raf (BRAF) V600E mutation compared with group A. In multivariable analysis, malignant ultrasonographic features and tumor size ≤3.0 cm were independent predictive factors for group B. Conclusion: FVPTCs >3.0 cm are unlikely to be diagnosed as category V or VI. Clinicians should keep FVPTC in mind and consider diagnostic lobectomy for the nodules regardless of FNA or ultrasonographic findings. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1467–E1471, 2016